Role of Speaker Cues in Attention Inference - Lee, Jin Joo; Breazeal, Cynthia; DeSteno, David (Frontiers in Robotics and AI, 2017)
Current state-of-the-art approaches to emotion recognition primarily focus on modeling the nonverbal expressions of the sole individual without reference to contextual elements like the co-presence of the partner. In this paper, we demonstrate that the accurate inference of listeners' social-emotional state of attention depends on also accounting for the nonverbal behaviors of their storytelling partner, namely their speaker cues. To gain a deeper understanding of the role of speaker cues in attention inference, we conduct investigations into real world interactions of children storytelling with their peers. Through in-depth analysis of human-human interaction data, we first identify nonverbal speaker cues (i.e., backchannel-inviting cues) and listener responses (i.e., backchannel feedback) to later demonstrate how speaker cues can modify the interpretation of attention-related backchannels as well as serve as a means to regulate the responsiveness of listeners. We then discuss the design implications of our findings toward our primary goal of developing attention recognition models for storytelling robots. Social robots can use speaker cues to form more accurate inferences about the attentive state of their human partner.